Muslim perspectives on advance care planning: a model for community engagement - Alya Abbas Heirali; Sidra Javed; Zaheed Damani; Rahim Kachra; Sabira Valiani; Al-Karim Walli; Philippe Couillard; Rose Geransar; Jessica Simon; Safiya Karim (Palliative Care and Social Practice, 2021)
Background: Advance care planning is the process of communicating and documenting a person’s future health care preferences. Despite its importance, knowledge of advance care planning is limited, especially among the Islamic community. In addition, little is known about how the Islamic community views advance care planning in the context of their religious and cultural beliefs. Objectives: We aimed to increase knowledge of the importance of advance care planning, to improve health care provider and public knowledge, and to encourage dialogue between the community and health care providers. Methods: We organized a community event and assembled a multi-disciplinary panel. Through a moderated discussion, the panel members offered their perspectives of advance care planning within a Muslim context. Results: Approximately 100 individuals attended the event including community members, health care providers, medical students, and faith leaders. More than 90% of respondents rated the event as very good or excellent, found the session useful and were encouraged to reflect further on advance care planning. Conclusion: This event was successful in raising awareness about advance care planning within the Islamic community as well as educating health care providers on Islamic views. This model of community and health care provider engagement may also be beneficial for other faith groups wishing to discuss advance care planning within their respective religious and cultural contexts.